Inclusion Body Disease in a Corallus hortulanus - Turchetti , Andréia Pereira; Tinoco , Herlandes Penha; Malta , Marcelo de Campos Cordeiro; Costa , Maria Elvira Loyola Teixeira da; Pessanha , Angela Tinoco; Soave , Semiramis Azevedo; Paixão, Tatiane Alves; Santos, Renato Lima (Brazilian Journal of Veterinary Pathology, 2013)
An adult male Amazon tree boa (Corallus hortulanus) from the Zoo-Botanical Foundation (Belo Horizonte, Brazil) died after a period of apathy and anorexia. Cachexia was the only significant gross finding. Numerous eosinophilic intracytoplasmic inclusion bodies were found in the liver, lungs, heart, testes, kidneys, and adipose tissue, compatible with the Inclusion Body Disease. The snake also had an undifferentiated metastatic sarcoma. In order to further characterize the inclusion bodies found in this case, transmission electronic microscopy was performed. Inclusion Body Disease affects boid snakes, causing regurgitation, anorexia and neurological signs that eventually lead to death. This is a challenging disease since its etiology, pathogenesis, and epidemiology are unknown, and therefore treatment is not effective. This is the first report of Inclusion Body Disease in boid snake in Brazil.